Synthesis of 1,4-benzothiazinones from acylpyruvic acids or furan-2,3-diones and o-aminothiophenol - Stepanova, Ekaterina E.; Dmitriev, Maksim V.; Maslivets, Andrey N. (Beilstein Journal of Organic Chemistry, 2020)
Two synthetic approaches to enaminones fused to 1,4-benzothiazin-2-one moiety, which can be interesting in studies on biological activity, chemosensors, and fluorescence, were developed via the reaction of furan-2,3-diones or acylpyruvic acids in the presence of carbodiimides with o-aminothiophenols. The target enaminones were formed together with pharmaceutically interesting 2-hydroxy-2H-1,4-benzothiazin-3(4H)-ones. A selective synthetic approach to 2-hydroxy-2H-1,4-benzothiazin-3(4H)-ones was developed via the solvent-switchable reaction of furan-2,3-diones with o-aminothiophenol. Preliminary biological assays (antimicrobial, acute toxicity) of the new compounds were carried out.
Keywords: acylpyruvic acid; 1,4-benzothiazine; cyclocondensation; diversity-oriented synthesis; furan-2,3-dione